Poverty Status in Afghanistan : A Profile Based on National Risk and Vulnerability Assessment 2007/08 - Islamic Republic of Afghanistan Ministry of Economy; World Bank (World Bank, Washington, DC, 2017)
Poverty reduction is one of the three key objectives of the Afghanistan national development strategy. The poverty profile is an important element in the information kit of the policymaker that helps focus policy to attain this objective. A poverty profile is standard methodology to describe the extent and nature of poverty in a country or region. It assesses the magnitude of poverty and its distribution across geographic and socioeconomic domains, provides information on the characteristics of the poor, illustrates the heterogeneity among the poor, and identifies correlates of poverty. The report describes the multidimensional nature of poverty by encompassing the nonmonetary dimensions of poverty, particularly education and health status, and vulnerability to shocks. Tables in the report are also disaggregated by region, income sources, gender, and many socioeconomic characteristics. In addition to providing a picture of the many dimensions of poverty, it is important to also recognize that the poverty estimates in this report are the first nationally representative, seasonally smoothed estimates of wellbeing for Afghanistan. Because previously no such existing estimates were available, the provision of these estimates in this report is new analysis that substantially fills key knowledge gaps in our understanding of the poverty situation in Afghanistan.